Alternative Dispute Resolution in Marine Pollution: Advancing Ecological Justice through the Polluter Pays Principle - Triana, Nita; Turistiati, Ade Tuti; Monk, Lincoln James Faikar (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
This study seeks to elucidate the challenges associated with compensation in marine pollution disputes through the lens of the Alternative Dispute Resolution (ADR) model. Governed by UUPPLH Number 32 of 2009, polluters are mandated to provide compensation for both affected parties and environmental restoration. However, the implementation of the ADR model in practice has seen polluters compensating only the affected communities, notably fishermen. This research endeavors to develop an ADR legal framework that encapsulates ecological justice, ensuring fairness for both society and the environment. The methodology employed in this study is non-doctrinal legal research, which involves analyzing legal phenomena within their social and cultural context. Findings from this research indicate that pollution disputes in the waters in Cilacap were resolved using the ADR model, with a disproportionate focus on compensating fishing communities. This results in environmental damage due to minimal environmental ADR legal framework grounded in the Polluter Pays principle. Such a framework should encompass legal provisions for environmental prevention, mitigation, and restoration. From a structural perspective, it is imperative to foster integration and connectivity between the community and ministries responsible for addressing marine environmental pollution, to facilitate effective environmental mitigation and restoration efforts. Additionally, in the realm of legal culture, there is a crucial need to cultivate legal awareness among the public regarding environmental conservation and management. This awareness should permeate all levels of society, including business entities, legislative bodies, the government, and law enforcement agencies. A robust legal system is essential for making ADR an equitable mechanism for resolving disputes, benefiting both victims of pollution and the environment.